2022
DOI: 10.1093/ofid/ofac120
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Infectious Diseases Elective for Early Clinical Medical Students on Their Internal Medicine Clerkship

Abstract: Background Early medical subspecialty training is an emerging trend in medical education. These electives are still rare for Early Clinical Medical Students (ECMS). We describe the introduction of an Infectious Disease (ID) inpatient consult rotation elective for ECMS. Methods In addition to seeing patients and rounding with the inpatient ID consult team, we created a supplemental curriculum to provide added support for ECMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…We do not find any correlation with hospital organizations, department facilities, and department heads. Our findings agree with earlier findings showing that tutors matter most in the satisfaction of clinical rotations [11,12]. Our findings are in partial agreement with earlier reports showing that other confounders matter less, such as the department premises (rs = 0.51), the department director (rs = 0.34), and the pedagogical atmosphere (rs = 0.38) [10]), but contrast another report showing that the aforementioned factors matter equally [9].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We do not find any correlation with hospital organizations, department facilities, and department heads. Our findings agree with earlier findings showing that tutors matter most in the satisfaction of clinical rotations [11,12]. Our findings are in partial agreement with earlier reports showing that other confounders matter less, such as the department premises (rs = 0.51), the department director (rs = 0.34), and the pedagogical atmosphere (rs = 0.38) [10]), but contrast another report showing that the aforementioned factors matter equally [9].…”
Section: Discussionsupporting
confidence: 92%
“…The student's satisfaction with the tutor-student relationship has been shown to contribute most to instruction rating [11]. Likewise, most students reported that the rotation was a useful educational experience and that the tutoring coach was one of the most valuable aspects of clinical rotation [12].…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor —We read with great interest the article by Sigler et al [ 1 ] published recently in this prestigious journal about the evaluation of the infectious disease elective for early clinical medical students in their internal medicine clerkship. This article evaluated self-reported learning and the level of satisfaction with the rotation using a Likert scale.…”
mentioning
confidence: 99%